Method and System for Directed Loading of Active Components in Dimethyl Carbonate Synthesis Catalysts
By pretreating and surface-modifying the porous silica-alumina composite oxide support, and combining atomic layer deposition and microwave irradiation techniques, directional loading of cerium oxide nanoparticles and directional bonding of palladium ions were achieved. This solved the problems of uneven distribution and insufficient stability of the active components of the catalyst in traditional methods, improved the performance and lifetime of the catalyst, and increased the synthesis efficiency of dimethyl carbonate.
Patent Information
- Application Number
- CN202511403894.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-29
- Publication Date
- 2025-12-02
- Estimated Expiration
- 2045-09-29
AI Technical Summary
In existing technologies, the uneven distribution and weak interaction of dimethyl carbonate synthesis catalysts on the support lead to short catalyst stability and lifespan. The technical problem with traditional methods is that the catalysts in existing technologies have long stability and lifespan. Traditional methods also make it difficult to accurately control the size and loading position of active components, which limits the improvement of catalyst performance.
A porous silica-alumina composite oxide support was used for pretreatment and surface modification. Cerium oxide nanoparticles were selectively loaded onto the inner wall of the pores through atomic layer deposition. Palladium ions were then directionally bonded to the cerium oxide nanoparticles using microwave irradiation technology to form a bifunctional catalytic active center with synergistic effect.
It significantly improved the overall performance and lifespan of the catalyst, enhanced its activity and stability, and improved the synthesis efficiency and product quality of dimethyl carbonate.
Smart Images

Figure CN120861037B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, and more particularly to a method and system for directional loading of active components in dimethyl carbonate synthesis catalysts. Background Technology
[0002] Dimethyl carbonate (DMC) is an important organic chemical raw material and green solvent, widely used in polycarbonates, coatings, lithium-ion battery electrolytes, and other fields. Currently, the industrial production of DMC mainly employs the carbon oxidative esterification method, which uses carbon monoxide and methanol as raw materials to synthesize DMC in the presence of a catalyst. The performance of the catalyst has a decisive impact on the reaction efficiency and product quality.
[0003] Traditional dimethyl carbonate synthesis catalysts are typically prepared using an impregnation method, where an active component solution is impregnated onto a porous support, followed by drying and calcination. However, this method has some drawbacks and limitations:
[0004] First, the uneven distribution of active components on the support surface makes them prone to agglomeration, resulting in low catalyst utilization and low activity.
[0005] Secondly, the interaction between the active component and the support is weak, and the component is easily lost during the reaction, affecting the stability and lifespan of the catalyst.
[0006] Finally, traditional methods have difficulty in precisely controlling the size and loading location of active components, failing to fully utilize the advantages of the pore structure of the support, and limiting the improvement of catalyst performance. Summary of the Invention
[0007] The present invention provides a method and system for directional loading of active components in a catalyst for the synthesis of dimethyl carbonate, which can solve the problems in the prior art.
[0008] A first aspect of the present invention provides a method for directional loading of the active component of a dimethyl carbonate synthesis catalyst, comprising:
[0009] The porous silicon-aluminum composite oxide support was calcined under vacuum at a temperature range of 500-600℃ for 4-6 hours to obtain the pretreated support.
[0010] The pretreated support was placed in a reaction vessel containing dichloromethane solvent, a silane coupling agent was added, and the reaction was stirred at 60-80℃ for 2-3 hours. The mixture was then filtered and vacuum dried to obtain the surface-modified support.
[0011] Atomic layer deposition was used to introduce cerium oxide precursor into the pores of a surface-modified support, and the size of cerium oxide nanoparticles was controlled to be 3-5 nm. This allowed the cerium oxide nanoparticles to be selectively loaded onto the inner walls of the pores of the surface-modified support, thus obtaining the first intermediate.
[0012] The first intermediate was dispersed in an ethanol solution, potassium nitrate solution was added, and the mixture was ultrasonically dispersed for 30-40 minutes at a pH of 7-8.
[0013] A complexing agent and palladium chloride solution were added to the above dispersion. The palladium ions were then irradiated with microwaves to induce directional bonding between the palladium ions and cerium oxide nanoparticles. The microwave power was controlled at 400-600W and the irradiation time was 10-15 minutes to obtain the second intermediate.
[0014] The second intermediate was reduced in a nitrogen atmosphere at a temperature range of 300-400℃ for 2-3 hours, then filtered, washed with water, and dried to obtain the dimethyl carbonate synthesis catalyst.
[0015] Atom layer deposition (ALD) is used to introduce a cerium oxide precursor into the pores of a surface-modified support. The size of the cerium oxide nanoparticles is controlled to be 3-5 nm, allowing the cerium oxide nanoparticles to be selectively loaded onto the inner walls of the pores of the surface-modified support, resulting in a first intermediate comprising:
[0016] The tetravalent cerium complex precursor is introduced, purged with nitrogen, oxidized with ozone, and purged a second time 80-120 times to form 3-5 nanometer nanoparticles on the inner wall of the pores of the modified carrier, thus obtaining the first intermediate. The concentration ratio of the cerium oxide nanoparticles inside and outside the pores is greater than 15.
[0017] The process includes introducing the tetravalent cerium complex precursor, nitrogen purging, ozone oxidation, and secondary purging.
[0018] The porous silica-alumina composite oxide support is surface modified with a silane coupling agent to obtain a modified support with silane groups on the surface. The pore size of the modified support is distributed in the range of 5-7 nanometers.
[0019] The modified support was placed in an atomic layer deposition reaction chamber at a temperature of 200°C, and a tetravalent cerium complex precursor was introduced. The vapor pressure of the tetravalent cerium complex precursor was controlled to be 0.13 kPa, so that the tetravalent cerium complex precursor could selectively coordinate with the silane groups on the surface of the modified support. The pulse introduction time was 3 seconds.
[0020] High-purity nitrogen gas was introduced at a flow rate of 100 standard cubic centimeters per minute for 10 seconds to purge the tetravalent cerium complex precursor that had not undergone coordination.
[0021] Ozone at a concentration of 150 g / m³ was introduced to carry out an oxidation reaction, with a pulse introduction time of 4 seconds, converting the coordinated tetravalent cerium complex precursor into cerium oxide.
[0022] High-purity nitrogen gas was introduced again at a flow rate of 100 standard cubic centimeters per minute for a second purging, and the purging time was 12 seconds.
[0023] The modified support is placed in an atomic layer deposition reaction chamber at a temperature of 200°C, and a tetravalent cerium complex precursor is introduced. The vapor pressure of the tetravalent cerium complex precursor is controlled to be 0.13 kPa, so that the tetravalent cerium complex precursor selectively coordinates with the silane groups on the surface of the modified support, including:
[0024] A modified support with silane groups on its surface is placed in an atomic layer deposition (ALD) chamber at 200°C. A tetravalent cerium complex precursor is introduced into the ALD chamber, and the vapor pressure of the tetravalent cerium complex precursor is controlled to be 0.13 kPa. The tetravalent cerium complex precursor is coordinated with the silane groups on the surface of the modified support through coordination bonds to form a tetravalent cerium-silane coordination compound. The tetravalent cerium complex precursor only coordinates with the silane groups on the inner wall of the pores of the modified support, and the concentration ratio of the tetravalent cerium-silane coordination compound inside and outside the pores is greater than 15.
[0025] A complexing agent and palladium chloride solution were added to the above dispersion. Microwave irradiation was used to induce directional bonding between palladium ions and cerium oxide nanoparticles. The microwave power was controlled at 400-600 W, and the irradiation time was 10-15 minutes to obtain the second intermediate, which includes:
[0026] Add 0.01-0.02 mol / L of ethylenediaminetetraacetic acid complexing agent to a dispersion containing cerium oxide nanoparticles, and stir and disperse at room temperature for 10 minutes to form a stable complexing system.
[0027] Palladium chloride solution was added dropwise to the complexing system, and the molar ratio of palladium ions to the ethylenediaminetetraacetic acid complexing agent was controlled at 1:1.2. The mixture was stirred for 15 minutes to obtain a palladium-complexing agent dispersion.
[0028] The palladium-complexing agent dispersion was placed in a microwave reactor and irradiated with microwaves at a frequency of 2.45 GHz. The microwave power was controlled to linearly adjust the temperature rise within the range of 400-600 W, so that the reaction temperature increased at a rate of 5-8 degrees Celsius per minute.
[0029] Maintain microwave irradiation for 10-15 minutes to promote directional bonding between the palladium-complexing agent complex and the surface of the cerium oxide nanoparticles;
[0030] The reaction product was cooled to room temperature, centrifuged, washed three times with deionized water, and vacuum dried for 4 hours to obtain a palladium-cerium oxide composite catalyst with an interfacial binding energy of 180-220 kJ / mol, which was used as the second intermediate.
[0031] Promoting the directional bonding of the palladium-complexing agent complex to the surface of the cerium oxide nanoparticles includes:
[0032] The palladium-complexing agent complex forms palladium-oxygen-cerium bonds with a bond length of 0.198-0.205 nm on the surface of the cerium oxide nanoparticles. The interfacial contact angle of the palladium-oxygen-cerium bonds is 75-85 degrees, and the interfacial binding energy of the palladium-oxygen-cerium bonds is 180-220 kJ / mol.
[0033] A second aspect of the present invention provides a directional loading system for the active component of a dimethyl carbonate synthesis catalyst, comprising:
[0034] The first unit is used to calcine the porous silicon-aluminum composite oxide support under vacuum conditions at a temperature range of 500-600℃ for 4-6 hours to obtain a pretreated support.
[0035] The second unit is used to place the pretreated support in a reaction vessel containing dichloromethane solvent, add silane coupling agent, stir and react in a temperature range of 60-80℃ for 2-3 hours, filter and vacuum dry to obtain a surface-modified support.
[0036] The third unit is used to introduce the cerium oxide precursor into the pores of the surface-modified support using an atomic layer deposition process, control the size of the cerium oxide nanoparticles to be 3-5 nm, and selectively load the cerium oxide nanoparticles onto the inner wall of the pores of the surface-modified support to obtain the first intermediate.
[0037] The fourth unit is used to disperse the first intermediate in an ethanol solution, add potassium nitrate solution, and ultrasonically disperse for 30-40 minutes at a pH of 7-8.
[0038] The fifth unit is used to add a complexing agent and palladium chloride solution to the above dispersion, and to use microwave irradiation technology to make palladium ions and cerium oxide nanoparticles undergo directional bonding. The microwave power is controlled at 400-600W and the irradiation time is 10-15 minutes to obtain the second intermediate.
[0039] Unit 6 is used to reduce the second intermediate in a nitrogen atmosphere at a temperature range of 300-400℃ for 2-3 hours, followed by filtration, washing with water, and drying to obtain a dimethyl carbonate synthesis catalyst.
[0040] A third aspect of the embodiments of the present invention,
[0041] An electronic device is provided, comprising:
[0042] processor;
[0043] Memory used to store processor-executable instructions;
[0044] The processor is configured to invoke instructions stored in the memory to execute the aforementioned method.
[0045] Fourth aspect of the present invention,
[0046] A computer-readable storage medium is provided, having stored thereon computer program instructions that, when executed by a processor, implement the aforementioned method.
[0047] The beneficial effects of this application are as follows:
[0048] First, by pretreating and surface-modifying the porous silica-alumina composite oxide support, the stability and functionality of the support are enhanced, laying the foundation for the subsequent directional loading of active components. This treatment method can significantly improve the overall performance and lifetime of the catalyst.
[0049] Secondly, atomic layer deposition (ALD) was used to selectively load cerium oxide nanoparticles onto the pore walls of the modified support, with precise size control, significantly improving the specific surface area and the dispersion of active sites of the catalyst. This method can effectively enhance the catalytic efficiency and selectivity of the catalyst.
[0050] Finally, palladium ions were directionally bonded to cerium oxide nanoparticles using microwave irradiation, and then reduced under specific conditions to form a bifunctional catalytic active center with a synergistic effect. This unique structural design significantly enhances the activity and stability of the catalyst, which is beneficial for improving the synthesis efficiency and product quality of dimethyl carbonate. Attached Figure Description
[0051] Figure 1 This is a schematic diagram of the process for the directional loading of the active component of the catalyst for the synthesis of dimethyl carbonate, according to an embodiment of the present invention. Detailed Implementation
[0052] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0053] The technical solution of the present invention will be described in detail below with reference to specific embodiments. These specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments.
[0054] Figure 1 This is a schematic diagram of the process for the directional loading of the active component of the dimethyl carbonate synthesis catalyst according to an embodiment of the present invention, as shown below. Figure 1 As shown, the method includes:
[0055] The porous silicon-aluminum composite oxide support was calcined under vacuum at a temperature range of 500-600℃ for 4-6 hours to obtain the pretreated support.
[0056] The pretreated support was placed in a reaction vessel containing dichloromethane solvent, a silane coupling agent was added, and the reaction was stirred at 60-80℃ for 2-3 hours. The mixture was then filtered and vacuum dried to obtain the surface-modified support.
[0057] Atomic layer deposition was used to introduce cerium oxide precursor into the pores of a surface-modified support, and the size of cerium oxide nanoparticles was controlled to be 3-5 nm. This allowed the cerium oxide nanoparticles to be selectively loaded onto the inner walls of the pores of the surface-modified support, thus obtaining the first intermediate.
[0058] The first intermediate was dispersed in an ethanol solution, potassium nitrate solution was added, and the mixture was ultrasonically dispersed for 30-40 minutes at a pH of 7-8.
[0059] A complexing agent and palladium chloride solution were added to the above dispersion. The palladium ions were then irradiated with microwaves to induce directional bonding between the palladium ions and cerium oxide nanoparticles. The microwave power was controlled at 400-600W and the irradiation time was 10-15 minutes to obtain the second intermediate.
[0060] The second intermediate was reduced in a nitrogen atmosphere at a temperature range of 300-400℃ for 2-3 hours, then filtered, washed with water, and dried to obtain the dimethyl carbonate synthesis catalyst.
[0061] In one optional embodiment, an atomic layer deposition process is used to introduce a cerium oxide precursor into the pores of a surface-modified support, controlling the size of the cerium oxide nanoparticles to be 3-5 nm, so that the cerium oxide nanoparticles are selectively loaded onto the inner wall of the pores of the surface-modified support, to obtain a first intermediate comprising:
[0062] The tetravalent cerium complex precursor is introduced, purged with nitrogen, oxidized with ozone, and purged a second time 80-120 times to form 3-5 nanometer nanoparticles on the inner wall of the pores of the modified carrier, thus obtaining the first intermediate. The concentration ratio of the cerium oxide nanoparticles inside and outside the pores is greater than 15.
[0063] This embodiment provides a method for preparing cerium oxide nanoparticles using atomic layer deposition (ALD), which allows for precise control of the size and distribution of the cerium oxide nanoparticles. The specific steps are as follows:
[0064] First, a suitable surface modification support is selected. Porous materials such as porous silica, alumina, or zeolite can be used as supports. In this embodiment, a mesoporous silica-alumina composite oxide with an average pore size of 10 nm is selected as the support.
[0065] The support was surface modified. The support was immersed in a 3 wt% solution of 3-aminopropyltriethoxysilane in ethanol and stirred at 60 °C for 4 hours. The modified support was then washed three times with ethanol and vacuum dried at 80 °C for 12 hours to obtain the surface-modified support.
[0066] Prepare a tetravalent cerium complex precursor solution. Dissolve tetra(isopropanol)cerium in anhydrous ethanol to prepare a 0.1 mol / L solution.
[0067] The modified support was placed in an atomic layer deposition reactor. The reactor temperature was set at 250°C and the pressure at 1 Torr.
[0068] A tetravalent cerium complex precursor solution vapor is introduced and held for 30 seconds to allow the precursor molecules to adsorb onto the carrier surface.
[0069] The reaction chamber was purged with high-purity nitrogen (99.999%) for 60 seconds to remove unreacted precursor molecules.
[0070] Introduce ozone and maintain for 30 seconds to oxidize the adsorbed precursor molecules.
[0071] Purge again with nitrogen for 60 seconds to remove reaction products and excess ozone.
[0072] Repeat the above four steps (introduce precursor - purge - ozone oxidation - purge) 100 times to form cerium oxide nanoparticles on the inner wall of the carrier pores.
[0073] In practice, the size of cerium oxide nanoparticles can be controlled by adjusting parameters such as reaction temperature, pressure, precursor concentration, and reaction time. In this embodiment, by optimizing the reaction conditions, the average size of the cerium oxide nanoparticles is controlled to be around 4 nm.
[0074] To verify the size and distribution of cerium oxide nanoparticles, transmission electron microscopy (TEM) was used for characterization. TEM results showed that cerium oxide nanoparticles were uniformly distributed on the inner wall of the support pores, with a particle size distribution in the range of 3-5 nm and an average particle size of 4.2 nm.
[0075] To determine the distribution of cerium oxide nanoparticles inside and outside the pores, elemental analysis was performed using energy-dispersive X-ray spectroscopy (EDS). EDS analysis was conducted at multiple locations on the surface and inside the support. The results showed that the cerium content inside the pores was significantly higher than that on the outer surface, with a calculated concentration ratio of approximately 18:1.
[0076] Furthermore, the crystal structure of cerium oxide nanoparticles can be determined by X-ray diffraction (XRD) analysis. The XRD pattern shows typical characteristic peaks of the cerium oxide cubic fluorite structure, with relatively broad peak widths, further confirming the formation of nanoparticles.
[0077] The specific surface area and pore structure of the samples were tested using nitrogen adsorption-desorption isotherms. The results showed that, compared with the original support, the specific surface area of the sample loaded with cerium oxide nanoparticles decreased slightly, from 800 m² / g to 750 m² / g, and the pore volume also decreased accordingly, indicating that the cerium oxide nanoparticles were successfully loaded into the pores.
[0078] To further optimize the reaction conditions, the number of atomic layer deposition cycles can be adjusted. For example, when the number of cycles increased to 120, the average size of the cerium oxide nanoparticles increased to 5.5 nm, and some particles began to grow on the outer surface of the support. When the number of cycles decreased to 80, the average size of the cerium oxide nanoparticles decreased to 3.2 nm, but the distribution uniformity decreased slightly. Therefore, 100 cycles yielded the best size control and distribution uniformity.
[0079] The reaction temperature also significantly affects the growth of cerium oxide nanoparticles. When the temperature drops to 200℃, the reaction rate decreases significantly, requiring an increase in the number of cycles to achieve the same loading. When the temperature rises to 300℃, the growth rate of cerium oxide nanoparticles accelerates, but the size uniformity deteriorates. Therefore, 250℃ is a more ideal reaction temperature.
[0080] Precursor concentration is also an important parameter. When the concentration is reduced to 0.05 mol / L, the number of cycles needs to be increased to achieve the same loading. When the concentration is increased to 0.2 mol / L, although the number of cycles can be reduced, the particle size controllability deteriorates. Therefore, a concentration of 0.1 mol / L achieves a good balance between reaction efficiency and size control.
[0081] By adjusting these reaction parameters, the size, distribution, and loading of cerium oxide nanoparticles can be precisely controlled. For example, by lowering the reaction temperature to 230°C and increasing the number of cycles to 110, cerium oxide nanoparticles with an average size of 3.5 nm can be obtained. By increasing the reaction temperature to 270°C and reducing the number of cycles to 90, cerium oxide nanoparticles with an average size of 4.8 nm can be obtained.
[0082] The cerium oxide nanoparticles prepared by this method have the characteristics of small particle size, uniform distribution, and selective loading, and can be widely used in catalysis, adsorption, sensing and other fields. For example, when used as a catalyst for diesel engine exhaust gas treatment, due to the small size and good dispersibility of the nanoparticles, they exhibit excellent low-temperature activity and thermal stability, and the conversion rate of CO and hydrocarbons can reach more than 95% at 400℃.
[0083] In one optional embodiment, the process of introducing the tetravalent cerium complex precursor, nitrogen purging, ozone oxidation, and secondary purging includes:
[0084] The porous silica-alumina composite oxide support is surface modified with a silane coupling agent to obtain a modified support with silane groups on the surface. The pore size of the modified support is distributed in the range of 5-7 nanometers.
[0085] The modified support was placed in an atomic layer deposition reaction chamber at a temperature of 200°C, and a tetravalent cerium complex precursor was introduced. The vapor pressure of the tetravalent cerium complex precursor was controlled to be 0.13 kPa, so that the tetravalent cerium complex precursor could selectively coordinate with the silane groups on the surface of the modified support. The pulse introduction time was 3 seconds.
[0086] High-purity nitrogen gas was introduced at a flow rate of 100 standard cubic centimeters per minute for 10 seconds to purge the tetravalent cerium complex precursor that had not undergone coordination.
[0087] Ozone at a concentration of 150 g / m³ was introduced to carry out an oxidation reaction, with a pulse introduction time of 4 seconds, converting the coordinated tetravalent cerium complex precursor into cerium oxide.
[0088] High-purity nitrogen gas was introduced again at a flow rate of 100 standard cubic centimeters per minute for a second purging, and the purging time was 12 seconds.
[0089] Porous silicon-aluminum composite oxide was selected as the carrier material. This silicon-aluminum composite oxide carrier has a specific surface area of 500-600 m² / g and a pore volume of 0.8-1.0 cm³ / g. Nitrogen physical adsorption-desorption tests confirmed that the pore size distribution of the selected silicon-aluminum composite oxide carrier is mainly concentrated in the range of 5-7 nm. This mesoporous structure is beneficial for the uniform dispersion and loading of subsequent metal precursors.
[0090] Before atomic layer deposition (ALD), the surface of the silicon-aluminum composite oxide support needs to be modified. The specific procedure is as follows: 10 g of the silicon-aluminum composite oxide support is placed in a 250 mL three-necked flask, and 150 mL of anhydrous toluene is added as a solvent. The mixture is stirred thoroughly under nitrogen protection. Then, 15 mL of 3-aminopropyltriethoxysilane (APTES) is slowly added dropwise as a silane coupling agent, and the mixture is refluxed at 80 °C for 6 hours. After the reaction is complete, the product is filtered, washed three times successively with toluene and ethanol, and finally dried under vacuum at 60 °C for 12 hours to obtain a modified silicon-aluminum composite oxide support with aminopropyl silane groups on its surface. Infrared spectroscopy analysis confirms that amino functional groups were successfully introduced into the surface of the modified support, with a significant NH stretching vibration absorption peak appearing at 3300-3500 cm⁻¹.
[0091] The modified silicon-aluminum composite oxide support was placed in the reaction chamber of an atomic layer deposition apparatus, and the temperature of the reaction chamber was controlled at 200℃. Tetra-(2,2,6,6-tetramethyl-3,5-heptadecyl)cerium (Ce(TMHD)4) was selected as the tetravalent cerium complex precursor and loaded into a precursor source tank, with the source tank temperature controlled at 150℃. At this temperature, the vapor pressure of the tetravalent cerium complex precursor reached 0.13 kPa.
[0092] The atomic layer deposition process is carried out in the following cyclic steps:
[0093] The valve of the precursor source tank was opened, and the vapor of the tetravalent cerium complex precursor was introduced into the reaction chamber, with the pulse introduction time precisely controlled to 3 seconds. During this stage, the tetravalent cerium complex precursor molecules selectively coordinate with the aminopropylsilyl groups on the surface of the modified support, forming a stable coordination compound. XPS analysis showed that cerium mainly exists in the +4 valence form at this point, with characteristic peaks in the Ce 3d orbitals at approximately 882.5 and 901.1 eV.
[0094] Close the precursor source tank valve and purge with high-purity nitrogen gas (purity ≥99.999%) at a flow rate of 100 standard cubic centimeters per minute for 10 seconds. This step aims to remove uncoordinated tetravalent cerium complex precursors from the reaction chamber, preventing gas-phase side reactions and ensuring the self-limiting characteristics of atomic layer deposition. Mass spectrometry monitoring of the exhaust gas composition confirms that the uncoordinated precursors have been completely removed after 10 seconds.
[0095] Ozone at a concentration of 150 g / m³ was introduced for oxidation, with a pulse duration of 4 seconds. As a strong oxidant, ozone effectively oxidized the organic ligands in the coordinated tetravalent cerium complex precursor, converting them into cerium oxide (CeO₂). In-situ infrared spectroscopy revealed that during ozone oxidation, the CH and C=O stretching vibration peaks of the organic ligands gradually weakened, while the characteristic peaks of the Ce-O bond gradually increased in the 400-500 cm⁻¹ region, indicating that the organic ligands were successfully oxidized and removed, forming a cerium oxide structure.
[0096] A second purging was performed by introducing high-purity nitrogen gas at a flow rate of 100 standard cubic centimeters per minute for 12 seconds. The purpose of the second purging was to remove residual ozone and organic byproducts from the oxidation reaction from the reaction chamber, preparing for the next deposition cycle.
[0097] The above four steps constitute a complete atomic layer deposition cycle. By repeating this cycle 50 times, a cerium oxide film with a thickness of approximately 2 nanometers can be deposited on the surface of the modified silicon-aluminum composite oxide support. High-resolution transmission electron microscopy revealed that the prepared cerium oxide exhibits a highly dispersed nanoparticle state, with particle sizes ranging from 1.5 to 2.5 nanometers and a uniform distribution. X-ray diffraction analysis showed that the deposited cerium oxide has a cubic fluorite structure, with characteristic diffraction peaks corresponding to the (111), (200), (220), and (311) crystal planes appearing at 2θ = 28.5°, 33.1°, 47.5°, and 56.3°.
[0098] The cerium oxide / silicon-aluminum composite oxide material prepared by the above method has a cerium oxide loading of 8.5% by weight and a specific surface area of 450 m² / g. The cerium oxide nanoparticles expose a large number of (111) crystal planes, which contain abundant oxygen vacancies, beneficial for catalytic reactions. In CO oxidation tests, this material achieved a CO conversion rate of over 90% at 150℃, demonstrating excellent low-temperature catalytic performance.
[0099] The advantage of this method is that it achieves high dispersion of cerium oxide nanoparticles on the carrier surface through atomic layer deposition technology, avoiding the particle agglomeration problem that is easily caused by traditional impregnation methods. At the same time, through surface modification and precise control of reaction parameters, the uniformity and high activity of cerium oxide nanoparticles are ensured.
[0100] In one optional embodiment, the modified support is placed in an atomic layer deposition reaction chamber at a temperature of 200°C, and a tetravalent cerium complex precursor is introduced. The vapor pressure of the tetravalent cerium complex precursor is controlled to be 0.13 kPa, so that the tetravalent cerium complex precursor selectively coordinates with the silane groups on the surface of the modified support, including:
[0101] A modified support with silane groups on its surface is placed in an atomic layer deposition (ALD) chamber at 200°C. A tetravalent cerium complex precursor is introduced into the ALD chamber, and the vapor pressure of the tetravalent cerium complex precursor is controlled to be 0.13 kPa. The tetravalent cerium complex precursor is coordinated with the silane groups on the surface of the modified support through coordination bonds to form a tetravalent cerium-silane coordination compound. The tetravalent cerium complex precursor only coordinates with the silane groups on the inner wall of the pores of the modified support, and the concentration ratio of the tetravalent cerium-silane coordination compound inside and outside the pores is greater than 15.
[0102] Taking mesoporous silica-alumina composite oxide as an example, the surface modification of the support can be carried out using the following steps: Take 5 g of mesoporous silica-alumina composite oxide, place it in 100 mL of dry toluene, add 2 g of 3-aminopropyltriethoxysilane (APTES), and reflux under nitrogen protection for 12 hours. After the reaction is complete, filter the product, wash it three times successively with toluene and ethanol, and dry it under vacuum at 80 °C for 12 hours to obtain a modified silica-alumina composite oxide with -NH2 groups on the surface. Subsequently, take 4 g of the above product, place it in 100 mL of dry tetrahydrofuran, add 1.5 g of (3-mercaptopropyl)trimethoxysilane, and reflux under nitrogen protection for 10 hours. After the reaction is complete, filter the product, wash it three times successively with tetrahydrofuran and ethanol, and dry it under vacuum at 80 °C for 12 hours to obtain a modified support with both -NH2 and -SH groups on the surface.
[0103] Infrared spectroscopy confirmed the successful introduction of silane groups onto the modified support surface. Absorption peaks for CH stretching vibrations at 2950–2850 cm⁻¹ and Si-C absorption peaks at 1450–1400 cm⁻¹ indicated successful grafting of silane groups onto the support surface. X-ray photoelectron spectroscopy (XPS) revealed characteristic Si 2p, N 1s, and S 2p peaks on the modified support surface, further confirming the presence of silane groups. Elemental analysis determined the grafting density of silane groups on the modified support surface to be 1.2 mmol / g.
[0104] The modified support was placed in an atomic layer deposition reaction chamber for selective coordination of tetravalent cerium complexes. The specific procedure is as follows:
[0105] Two grams of modified support with silane groups on its surface were evenly spread on the substrate tray of the atomic layer deposition reactor, ensuring that the sample thickness did not exceed 2 mm to guarantee that the precursor could fully contact all support particles. The reaction chamber was evacuated to 1 × 10^-3 Pa, and the temperature was simultaneously raised to 200 °C and maintained for 1 hour to remove moisture and other impurities adsorbed on the support surface.
[0106] While maintaining the reaction chamber temperature at 200°C, high-purity nitrogen (≥99.999% purity) was introduced as the carrier gas at a flow rate controlled at 20 standard cubic centimeters per minute. Subsequently, the tetravalent cerium complex precursor tetra(2,2,6,6-tetramethyl-3,5-heptadecyl)cerium (Ce(TMHD)4) was placed in a precursor container and heated to 160°C to generate sufficient vapor pressure. Using a precise mass flow controller and pressure control system, the Ce(TMHD)4 precursor vapor was introduced into the reaction chamber, and its vapor pressure within the chamber was stabilized at 0.13 kPa (approximately 1 Torr).
[0107] In this process, cerium atoms in the Ce(TMHD)4 molecule selectively coordinate with silane groups (-NH2 and -SH) on the surface of the modified support. Specifically, the cerium atom, acting as a Lewis acid, forms coordination bonds with the N and S atoms (Lewis bases) in the silane group. The pulse duration is controlled at 30 seconds to ensure that the precursor diffuses sufficiently into the pores of the support and reacts fully with the surface silane groups. After the pulse ends, the reaction chamber is purged with high-purity nitrogen gas (flow rate 40 standard cubic centimeters / minute) for 60 seconds to remove unreacted precursors and reaction byproducts.
[0108] Repeat the pulse-purge cycle five times to ensure that the silane groups on the support surface react fully with the tetravalent cerium complex precursor. Throughout the process, the temperature of the reaction chamber is kept stable at 200±2℃, and the pressure fluctuation does not exceed ±0.01 kPa.
[0109] Through this process, the tetravalent cerium complex precursor selectively coordinates with the silane groups on the inner wall of the modified support pores, forming tetravalent cerium-silane coordination compounds. Due to the curvature and spatial confinement effects of the inner wall of the pores, the coordination between the silane groups inside the pores and the tetravalent cerium complex precursor is more favorable; therefore, the tetravalent cerium-silane coordination compounds are mainly formed inside the pores of the support.
[0110] The distribution of tetravalent cerium-silane coordination compounds within the pores of the support was observed using transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDS). The results showed that tetravalent cerium was mainly distributed inside the pores, with almost no cerium on the outer surface. Quantitative analysis of the TEM-EDS images yielded a concentration ratio of 18.5 between the inside and outside of the pores, significantly higher than the target value of 15.
[0111] X-ray absorption near-edge structure (XANES) analysis confirmed that the valence state of cerium in the sample was +4, indicating that the tetravalent cerium complex precursor maintained its original valence state during coordination. X-ray photoelectron spectroscopy (XPS) analysis showed characteristic satellite peaks in the Ce 3d spectrum, further confirming the +4 valence state of cerium.
[0112] Fourier transform infrared (FTIR) spectroscopy analysis showed that the stretching vibration peaks of NH and SH in the silane group were significantly weakened in the sample after the coordination reaction, while characteristic absorption peaks of Ce-N and Ce-S coordination bonds appeared, confirming that coordination bonds were formed between tetravalent cerium and the silane group.
[0113] Through the detailed implementation steps described above, selective coordination of tetravalent cerium complexes on the surface of the modified support was successfully achieved. The tetravalent cerium-silane coordination compounds are mainly distributed inside the pores of the support, with a concentration ratio inside and outside the pores greater than 15, achieving the expected technical effect.
[0114] In one optional embodiment, a complexing agent and a palladium chloride solution are added to the above dispersion, and microwave irradiation technology is used to induce palladium ions to undergo directional bonding with cerium oxide nanoparticles. The microwave power is controlled at 400-600W, and the irradiation time is 10-15 minutes to obtain a second intermediate comprising:
[0115] Add 0.01-0.02 mol / L of ethylenediaminetetraacetic acid complexing agent to a dispersion containing cerium oxide nanoparticles, and stir and disperse at room temperature for 10 minutes to form a stable complexing system.
[0116] Palladium chloride solution was added dropwise to the complexing system, and the molar ratio of palladium ions to the ethylenediaminetetraacetic acid complexing agent was controlled at 1:1.2. The mixture was stirred for 15 minutes to obtain a palladium-complexing agent dispersion.
[0117] The palladium-complexing agent dispersion was placed in a microwave reactor and irradiated with microwaves at a frequency of 2.45 GHz. The microwave power was controlled to linearly adjust the temperature rise within the range of 400-600 W, so that the reaction temperature increased at a rate of 5-8 degrees Celsius per minute.
[0118] Continue microwave irradiation for 10-15 minutes to promote directional bonding between the palladium-complexing agent complex and the surface of the cerium oxide nanoparticles;
[0119] The reaction product was cooled to room temperature, centrifuged, washed three times with deionized water, and vacuum dried for 4 hours to obtain a palladium-cerium oxide composite catalyst with an interfacial binding energy of 180-220 kJ / mol, which was used as the second intermediate.
[0120] Specifically, ethylenediaminetetraacetic acid (EDTA) at a concentration of 0.015 mol / L was selected as the complexing agent. The EDTA solution was slowly added dropwise to the cerium oxide nanoparticle dispersion at room temperature (25°C). The dispersion was then stirred at 300 rpm for 10 minutes using a mechanical stirrer to form a stable complexing system. The purpose of this step was to ensure that EDTA and cerium oxide nanoparticles were fully bonded, providing a good foundation for the subsequent directional bonding of palladium ions.
[0121] Prepare a 0.01 mol / L palladium chloride solution and add it dropwise to the complexing system using a constant pressure titrator at a rate of 2 mL / min. Maintain the molar ratio of palladium ions to EDTA at 1:1.2, i.e., add 1.2 moles of EDTA for every 1 mole of palladium ions. During the addition, keep the pH of the solution between 6.5 and 7.0. After the addition is complete, continue stirring for 15 minutes to obtain a palladium-complexing agent dispersion. The purpose of this step is to ensure that the palladium ions and EDTA fully complex, forming a stable complex.
[0122] A microwave reactor with adjustable power was used, and the microwave frequency was set to 2.45 GHz. The microwave reactor was started, and the microwave power was linearly adjusted within the range of 400-600 watts. Specifically, the microwave power could be set to an initial 400 watts, increasing by 50 watts every 2 minutes until it reached 600 watts. This power adjustment method allowed the reaction temperature to rise steadily at a rate of 6°C per minute. Temperature monitoring was performed using an infrared thermometer to monitor changes in the reaction solution temperature in real time.
[0123] Microwave irradiation for 12 minutes promoted the directional bonding of the palladium-complexing agent complex with the surface of cerium oxide nanoparticles. During this process, microwave energy was absorbed by the reaction system, promoting the interaction between palladium ions and the active sites on the cerium oxide surface. Simultaneously, the presence of the EDTA complexing agent facilitated the uniform distribution of palladium ions on the cerium oxide surface, preventing aggregation.
[0124] After microwave irradiation, the reaction product was allowed to cool naturally to room temperature. The solid product was then separated by centrifugation at 8000 rpm for 20 minutes. The separated solid was washed three times with deionized water for 5 minutes each time to remove residual unreacted substances and impurities. The washed product was then placed in a vacuum drying oven and dried under vacuum at 60°C for 4 hours to obtain the final palladium-cerium oxide composite catalyst.
[0125] To verify the performance of the obtained catalyst, X-ray photoelectron spectroscopy (XPS) was used to test its interfacial binding energy. The test results showed that the interfacial binding energy of the prepared palladium-cerium oxide composite catalyst was 200 kJ / mol, which is within the ideal range of 180-220 kJ / mol, indicating that a stable chemical bond was formed between palladium and cerium oxide.
[0126] Furthermore, the microstructure of the catalyst can be observed using transmission electron microscopy (TEM). TEM images show that palladium nanoparticles are uniformly dispersed on the surface of cerium oxide nanoparticles, with a particle size distribution in the range of 2-5 nanometers. This uniformly dispersed structure is beneficial for improving the activity and stability of the catalyst.
[0127] To evaluate the practical performance of the catalyst, a model reaction can be selected for testing. For example, taking the methanol reforming to hydrogen production reaction as an example, at a reaction temperature of 250°C, using 1 gram of the prepared palladium-cerium oxide composite catalyst, the methanol conversion rate can reach 95%, and the hydrogen selectivity exceeds 98%. This result is superior to the palladium / cerium oxide catalyst prepared by the traditional impregnation method (under the same conditions, the methanol conversion rate is 85%, and the hydrogen selectivity is 95%).
[0128] This method can also optimize catalyst performance by adjusting microwave irradiation conditions. For example, the microwave power can be increased to 550 watts and the irradiation time extended to 14 minutes. Under these conditions, the average particle size of palladium nanoparticles in the catalyst can be further reduced to 1-3 nanometers, thereby improving catalytic activity. In the aforementioned methanol reforming reaction, the methanol conversion rate can be increased to 97%, and the hydrogen selectivity reaches 99%.
[0129] Furthermore, another advantage of this method is the ease with which the palladium loading can be adjusted. Catalysts with different palladium loadings can be prepared by changing the concentration of the palladium chloride solution. For example, reducing the palladium chloride solution concentration to 0.005 mol / L yields a catalyst with a palladium loading of 1%; increasing it to 0.02 mol / L yields a catalyst with a palladium loading of 5%. Catalysts with different loadings can be applied to different types of catalytic reactions, meeting diverse needs.
[0130] In summary, the method provided by this invention achieves directional bonding of palladium and cerium oxide nanoparticles using microwave irradiation technology, thus preparing a high-performance palladium-cerium oxide composite catalyst. This method is simple to operate, has a short reaction time, low energy consumption, and allows for precise control of the catalyst's structure and performance, providing a new approach for the preparation of highly efficient catalysts.
[0131] In one optional embodiment, promoting the directional bonding of the palladium-complexing agent complex to the surface of the cerium oxide nanoparticles includes:
[0132] The palladium-complexing agent complex forms palladium-oxygen-cerium bonds with a bond length of 0.198-0.205 nm on the surface of the cerium oxide nanoparticles. The interfacial contact angle of the palladium-oxygen-cerium bonds is 75-85 degrees, and the interfacial binding energy of the palladium-oxygen-cerium bonds is 180-220 kJ / mol.
[0133] The specific implementation methods for promoting the directional bonding of palladium-complexing agent complexes with the surface of cerium oxide nanoparticles are as follows:
[0134] First, prepare the palladium-complexing agent solution. Dissolve the palladium precursor, such as palladium chloride or palladium acetate, in a suitable solvent, such as water, ethanol, or tetrahydrofuran. Then add the selected complexing agent, such as ethylenediamine, 1,10-phenanthroline, or 2,2'-bipyridine. Control the molar ratio of palladium precursor to complexing agent to be 1:1 to 1:4. Stir and mix thoroughly to form the palladium-complexing agent solution.
[0135] Next, a suspension of cerium oxide nanoparticles is prepared. Cerium oxide nanoparticles can be synthesized using a hydrothermal method or a sol-gel method. Taking the hydrothermal method as an example, cerium nitrate is dissolved in deionized water, and sodium hydroxide or ammonia is added to adjust the pH to 10-12. The mixture is transferred to a high-pressure reactor and reacted at 180-200℃ for 12-24 hours. After cooling, the mixture is centrifuged and washed several times with water and ethanol to obtain cerium oxide nanoparticles. These nanoparticles are then dispersed in water or ethanol to prepare a suspension with a concentration of 0.1-1 wt%.
[0136] Then, the palladium-complexing agent solution was added dropwise to the cerium oxide nanoparticle suspension. The dropping rate was controlled at 0.5-2 mL per minute. Simultaneously, the mixture was vigorously stirred at 800-1200 rpm. After the addition was complete, stirring continued for 30-60 minutes to ensure sufficient contact between the palladium-complexing agent and the cerium oxide nanoparticles.
[0137] Next, the mixture is subjected to gentle heating. The temperature is slowly increased to 60-80℃ and maintained at a constant temperature with stirring for 2-4 hours. This step helps promote directional bonding between the palladium-complexing agent complex and the surface of cerium oxide nanoparticles. During heating, palladium atoms in the palladium-complexing agent complex form coordination bonds with oxygen atoms on the cerium oxide surface, while weak interactions may also occur between the complexing agent and the cerium oxide surface.
[0138] To further enhance the bonding effect, the mixture can be ultrasonically treated. The mixture is transferred to an ultrasonic cleaner and ultrasonically treated at a frequency of 40-60 kHz for 30-60 minutes. The cavitation effect of ultrasound can provide a localized high-temperature, high-pressure environment, promoting the formation of palladium-oxygen-cerium bonds.
[0139] Subsequently, the mixture was centrifuged. The solid product was separated by centrifugation at 6000-8000 rpm for 15-20 minutes. It was then washed alternately with deionized water and ethanol 3-5 times to remove unbonded palladium-complexing agent complexes. Finally, the product was vacuum-dried at 60℃ for 12 hours to obtain cerium oxide nanoparticles with palladium-complexing agent complexes directionally bonded.
[0140] To verify the formation of the palladium-oxygen-cerium bond and its structural parameters, various characterization methods can be employed. First, high-resolution transmission electron microscopy (HRTEM) is used to observe the microstructure of the sample. Oxygen can be clearly observed in the HRTEM images.
[0141] The dimethyl carbonate synthesis catalyst active component directional loading system of this invention includes:
[0142] The first unit is used to calcine the porous silicon-aluminum composite oxide support under vacuum conditions at a temperature range of 500-600℃ for 4-6 hours to obtain a pretreated support.
[0143] The second unit is used to place the pretreated support in a reaction vessel containing dichloromethane solvent, add silane coupling agent, stir and react in a temperature range of 60-80℃ for 2-3 hours, filter and vacuum dry to obtain a surface-modified support.
[0144] The third unit is used to introduce the cerium oxide precursor into the pores of the surface-modified support using an atomic layer deposition process, control the size of the cerium oxide nanoparticles to be 3-5 nm, and selectively load the cerium oxide nanoparticles onto the inner wall of the pores of the surface-modified support to obtain the first intermediate.
[0145] The fourth unit is used to disperse the first intermediate in an ethanol solution, add potassium nitrate solution, and ultrasonically disperse for 30-40 minutes at a pH of 7-8.
[0146] The fifth unit is used to add a complexing agent and palladium chloride solution to the above dispersion, and to use microwave irradiation technology to make palladium ions and cerium oxide nanoparticles undergo directional bonding. The microwave power is controlled at 400-600W and the irradiation time is 10-15 minutes to obtain the second intermediate.
[0147] Unit 6 is used to reduce the second intermediate in a nitrogen atmosphere at a temperature range of 300-400℃ for 2-3 hours, followed by filtration, washing with water, and drying to obtain a dimethyl carbonate synthesis catalyst.
[0148] A third aspect of the embodiments of the present invention,
[0149] An electronic device is provided, comprising:
[0150] processor;
[0151] Memory used to store processor-executable instructions;
[0152] The processor is configured to invoke instructions stored in the memory to execute the aforementioned method.
[0153] Fourth aspect of the present invention,
[0154] A computer-readable storage medium is provided, having stored thereon computer program instructions that, when executed by a processor, implement the aforementioned method.
[0155] This invention can be a method, apparatus, system, and / or computer program product. The computer program product may include a computer-readable storage medium having computer-readable program instructions loaded thereon for performing various aspects of the invention.
[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for directional loading of active components in a catalyst for the synthesis of dimethyl carbonate, characterized in that, include: The porous silicon-aluminum composite oxide support was calcined under vacuum at a temperature range of 500-600℃ for 4-6 hours to obtain the pretreated support. The pretreated support was placed in a reaction vessel containing dichloromethane solvent, a silane coupling agent was added, and the reaction was stirred at 60-80℃ for 2-3 hours. The mixture was then filtered and vacuum dried to obtain the surface-modified support. Atomic layer deposition was used to introduce a cerium oxide precursor into the pores of a surface-modified support. The size of the cerium oxide nanoparticles was controlled to be 3-5 nm, so that the cerium oxide nanoparticles were selectively loaded onto the inner wall of the pores of the surface-modified support to obtain a first intermediate. The first intermediate was dispersed in an ethanol solution, potassium nitrate solution was added, and the mixture was ultrasonically dispersed for 30-40 minutes at a pH of 7-8 to obtain a dispersion. A complexing agent and palladium chloride solution were added to the above dispersion. Using microwave irradiation technology, palladium ions were directionally bonded to cerium oxide nanoparticles. The microwave power was controlled at 400-600W and the irradiation time was 10-15 minutes to obtain a second intermediate. The second intermediate was reduced in a nitrogen atmosphere at a temperature range of 300-400℃ for 2-3 hours. After filtration, washing with water, and drying, the dimethyl carbonate synthesis catalyst was obtained.
2. The method according to claim 1, characterized in that, Atom layer deposition (ALD) is used to introduce a cerium oxide precursor into the pores of a surface-modified support. The size of the cerium oxide nanoparticles is controlled to be 3-5 nm, allowing the cerium oxide nanoparticles to be selectively loaded onto the inner walls of the pores of the surface-modified support, resulting in a first intermediate comprising: The tetravalent cerium complex precursor is introduced, purged with nitrogen, oxidized with ozone, and purged a second time 80-120 times to form 3-5 nanometer nanoparticles on the inner wall of the pores of the modified carrier, thus obtaining the first intermediate. The concentration ratio of the cerium oxide nanoparticles inside and outside the pores is greater than 15.
3. The method according to claim 2, characterized in that, The process includes introducing the tetravalent cerium complex precursor, nitrogen purging, ozone oxidation, and secondary purging. The porous silica-alumina composite oxide support is surface modified with a silane coupling agent to obtain a modified support with silane groups on the surface. The pore size of the modified support is distributed in the range of 5-7 nanometers. The modified support was placed in an atomic layer deposition reaction chamber at a temperature of 200°C, and a tetravalent cerium complex precursor was introduced. The vapor pressure of the tetravalent cerium complex precursor was controlled to be 0.13 kPa, so that the tetravalent cerium complex precursor could selectively coordinate with the silane groups on the surface of the modified support. The pulse introduction time was 3 seconds. High-purity nitrogen gas was introduced at a flow rate of 100 standard cubic centimeters per minute for 10 seconds to purge the tetravalent cerium complex precursor that had not undergone coordination. Ozone at a concentration of 150 g / m³ was introduced to carry out an oxidation reaction, with a pulse introduction time of 4 seconds, converting the tetravalent cerium complex precursor in the coordinated state into cerium oxide. High-purity nitrogen gas was introduced again at a flow rate of 100 standard cubic centimeters per minute for a second purging, and the purging time was 12 seconds.
4. The method according to claim 3, characterized in that, The modified support is placed in an atomic layer deposition reaction chamber at a temperature of 200°C, and a tetravalent cerium complex precursor is introduced. The vapor pressure of the tetravalent cerium complex precursor is controlled to be 0.13 kPa, so that the tetravalent cerium complex precursor selectively coordinates with the silane groups on the surface of the modified support, including: A modified support with silane groups on its surface is placed in an atomic layer deposition (ALD) chamber at 200°C. A tetravalent cerium complex precursor is introduced into the ALD chamber, and the vapor pressure of the tetravalent cerium complex precursor is controlled to be 0.13 kPa. The tetravalent cerium complex precursor is coordinated with the silane groups on the surface of the modified support through coordination bonds to form a tetravalent cerium-silane coordination compound. The tetravalent cerium complex precursor only coordinates with the silane groups on the inner wall of the pores of the modified support, and the concentration ratio of the tetravalent cerium-silane coordination compound inside and outside the pores is greater than 15.
5. The method according to claim 1, characterized in that, A complexing agent and palladium chloride solution were added to the above dispersion. Microwave irradiation was used to induce directional bonding between palladium ions and cerium oxide nanoparticles. The microwave power was controlled at 400-600 W, and the irradiation time was 10-15 minutes to obtain the second intermediate, which includes: Add 0.01-0.02 mol / L of ethylenediaminetetraacetic acid complexing agent to a dispersion containing cerium oxide nanoparticles, and stir and disperse at room temperature for 10 minutes to form a stable complexing system. Palladium chloride solution was added dropwise to the complexing system, and the molar ratio of palladium ions to the ethylenediaminetetraacetic acid complexing agent was controlled at 1:1.
2. The mixture was stirred for 15 minutes to obtain a palladium-complexing agent dispersion. The palladium-complexing agent dispersion was placed in a microwave reactor and irradiated with microwaves at a frequency of 2.45 GHz. The microwave power was controlled to linearly adjust the temperature rise within the range of 400-600 W, so that the reaction temperature increased at a rate of 5-8 degrees Celsius per minute. Continue microwave irradiation for 10-15 minutes to promote directional bonding between the palladium-complexing agent complex and the surface of the cerium oxide nanoparticles; The reaction product was cooled to room temperature, centrifuged, washed three times with deionized water, and vacuum dried for 4 hours to obtain a palladium-cerium oxide composite catalyst with an interfacial binding energy of 180-220 kJ / mol, which was used as the second intermediate.
6. The method according to claim 5, characterized in that, Promoting the directional bonding of the palladium-complexing agent complex to the surface of the cerium oxide nanoparticles includes: The palladium-complexing agent complex forms palladium-oxygen-cerium bonds with a bond length of 0.198-0.205 nm on the surface of the cerium oxide nanoparticles. The interfacial contact angle of the palladium-oxygen-cerium bonds is 75-85 degrees, and the interfacial binding energy of the palladium-oxygen-cerium bonds is 180-220 kJ / mol.
7. A directional loading system for the active component of a dimethyl carbonate synthesis catalyst, used to implement the method as described in any one of claims 1-6, characterized in that, include: The first unit is used to calcine the porous silicon-aluminum composite oxide support under vacuum conditions at a temperature range of 500-600℃ for 4-6 hours to obtain a pretreated support. The second unit is used to place the pretreated support in a reaction vessel containing dichloromethane solvent, add silane coupling agent, stir and react in a temperature range of 60-80℃ for 2-3 hours, filter and vacuum dry to obtain a surface-modified support. The third unit is used to introduce the cerium oxide precursor into the pores of the surface-modified support using an atomic layer deposition process, control the size of the cerium oxide nanoparticles to be 3-5 nm, and selectively load the cerium oxide nanoparticles onto the inner wall of the pores of the surface-modified support to obtain the first intermediate. The fourth unit is used to disperse the first intermediate in an ethanol solution, add potassium nitrate solution, and ultrasonically disperse for 30-40 minutes at a pH of 7-8 to obtain a dispersion. The fifth unit is used to add a complexing agent and palladium chloride solution to the above dispersion, and to use microwave irradiation technology to make palladium ions and cerium oxide nanoparticles undergo directional bonding. The microwave power is controlled at 400-600W and the irradiation time is 10-15 minutes to obtain the second intermediate. Unit 6 is used to reduce the second intermediate in a nitrogen atmosphere at a temperature range of 300-400℃ for 2-3 hours, followed by filtration, washing with water, and drying to obtain a dimethyl carbonate synthesis catalyst.
8. An electronic device, characterized in that, include: processor; Memory used to store processor-executable instructions; The processor is configured to invoke instructions stored in the memory to execute the method according to any one of claims 1 to 6.
9. A computer-readable storage medium having computer program instructions stored thereon, characterized in that, When the computer program instructions are executed by the processor, they implement the method described in any one of claims 1 to 6.
Citation Information
Patent Citations
Supported palladium catalyst using palladium oxide as support and preparation method thereof
CN107456965A
Monatomic catalyst as well as preparation method and application thereof
CN119857477A